A perspective on the role of the pectoralis major flap in oral and maxillofacial oncology surgery. (6th January 2014) - Avery, C.
Abstract In general, the pedicled pectoralis major (PPM) flap has become a secondary choice for reconstruction in the developed world while remaining popular within the developing world. The pectoralis major flap is utilised in varying proportions as either the preferred reconstruction or for salvage reconstruction following free flap failure, further disease or complications. Refinements in surgical technique and an experienced surgeon may yield high total flap success rates with modest levels of wound complications. The pectoralis major flap is particularly useful with serious or multiple comorbidities, advanced disease, and previous surgery and/or chemoradiotherapy. It has primarily been used for reconstruction of extended radical neck dissection, posterolateral mandible, large glossectomy and oropharyngeal defects, and occasionally together with a free flap. A second free flap has increasingly been used after initial failure, particularly in the larger centres, but the PPM flap probably remains the most commonly used salvage option. The needs of the local population vary, survival outcomes are improving and patient choice may become an increasing factor in flap selection.